Glucose metabolism in quinine-treated patients with uncomplicated falciparum malaria. - Davis, T; Pukrittayakamee, S; Supanaranond, W; Looareesuwan, S; Krishna, S; Nagachinta, B; Turner, R; White, N (1990)
To investigate host and drug effects on glucose metabolism in acute falciparum malaria, 10 previously untreated, fasting Thai males with uncomplicated infections were given a 2-h intravenous glucose infusion (5 mg/kg ideal body weight min) with an infusion of quinine dihydrochloride (10 mg/kg body weight) during the second hour. Eight patients were restudied in convalescence. Fasting plasma glucose (mean +/- SD) and insulin (geometric mean (-SD to + SD] were higher during acute illness (5.5 +/- 1.0 mmol/l and 6.2 (5.0-7.7) mU/l) than in convalescence (4.2 +/- 0.25 mmol/l and 3.7 (2.1-6.7) mU/l; P less than 0.001 and P = 0.058 respectively). After 1 h, both plasma glucose (9.3 +/- 1.4 vs 7.5 +/- 0.8 mmol/l, P less than 0.001) and insulin (21.2 (13.8-32.5) vs 15.2 (11.2-20.8) mU/l, P = 0.089) remained higher during acute illness; mathematical model (CIGMA) assessment of these values indicated lower tissue insulin sensitivity on admission (97% (71-134] than in convalescence (139% (109-178), P less than 0.025) but normal beta-cell function on both occasions. Two-hour plasma glucose (9.5 +/- 2.0 mmol/l) and insulin (81.8 (51.5-129.9) mU/l) concentrations during acute illness were also significantly higher than in convalescence (7.2 +/- 1.2 mmol/l and 40.1 (23.5-68.4) mU/l, P less than or equal to 0.025) despite similar end-infusion free plasma quinine concentrations (P greater than 0.5). Basal plasma free fatty acid concentrations were increased in acute illness (0.68 +/- 0.24 vs 0.21 +/- 0.12 mmol/l, P less than 0.001) but fell to low levels at 2 h in both studies. These data suggest tissue insulin resistance and augmented quinine-stimulated insulin secretion in acute falciparum malaria, factors which are likely to influence the clinical situation in which malaria-associated hypoglycaemia occurs.